THE ROLE OF INDONESIAN ARMY (TNI) IN REDUCING THE 2001’S SAMPIT CONFLICT AS NATIONAL DEFENSE - Antonius Widodo; Muhammad Hadianto; Joni Widjayanto (UNISSULA, 2022)
The Sampit conflict that occurred in Sampit City, Kota Waringin Timur Regency (Kotim) between the Dayak and Madurese ethnic groups was an event that affected security stability in Indonesia. The purpose of writing in this study is to find out and analyze the role of the TNI in resolving the Ethnic Dayak and Ethnic Madurese conflicts in Sampit City, Kotim Regency as the implementation of national security as a form of safeguarding national security stability from foreign and domestic threats. The approach method used in this study was a normative juridical approach. The results of the research, among others, are that the factors that are the main causes of the conflict between the ethnic Dayak and the ethnic Madurese include cultural factors, social inequality factors and political factors. The role of the Indonesian Army (TNI) in the context of implementing national resilience in resolving the ethnic Dayak and Madurese conflicts in Sampit City, Kotim Regency is carried out by contributing to regional security providing positive benefits for conflict peace in relation to efforts to create a peaceful situation in Sampit City, Kotim Regency.